Evidence for Neutrals‐Foreshock Electrons Impact at Mars. Issue 9 (4th May 2018) - Mazelle, C. X.; Meziane, K.; Mitchell, D. L.; Garnier, P.; Espley, J. R.; Hamza, A. M.; Halekas, J.; Jakosky, B. M.
Abstract: Backstreaming electrons emanating from the bow shock of Mars reported from the Mars Atmosphere and Volatile EvolutioN/Solar Wind Electron Analyzer observations show a flux fall off with the distance from the shock. This feature is not observed at the terrestrial foreshock. The flux decay is observed only for electron energy E ≥ 29 eV. A reported recent study indicates that Mars foreshock electrons are produced at the shock in a mirror reflection of a portion of the solar wind electrons. In this context, and given that the electrons are sufficiently energetic to not be affected by the interplanetary magnetic field fluctuations, the observed flux decrease appears problematic. We investigate the possibility that the flux fall off with distance results from the impact of backstreaming electrons with Mars exospheric neutral hydrogen. We demonstrate that the flux fall off is consistent with the electron‐atomic hydrogen impact cross section for a large range of energy. A better agreement is obtained for energy where the impact cross section is the highest. One important consequence is that foreshock electrons can play an important role in the production of pickup ions at Mars far exosphere. Plain Language Summary: Energetic electrons emanating from the bow shock surrounding Mars by reflection of a small portion of the incident solar wind display an enigmatic decrease with the distance along the interplanetary magnetic field. We show for the first time from measurements by the MAVEN SWEA instrument that this is a consequence of the impact of those electrons on the neutrals atoms of the upper atmosphere of the planet. The signature of this process on the energetic electrons can be used as new diagnostic of the far upper atmosphere to better investigate the atmospheric escape. Key Points: Foreshock electrons flux declines with the distance from the shock of Mars Martian foreshock electron flux ratios are consistent with the electron‐neutral hydrogen impact cross section Foreshock electrons play an important role in the production of pickup ions in Mars distant exosphere